Peningkatan Literasi Keuangan Melalui Pembuatan Media Edukatif Bagi Siswa - Mulyati, Sri; Setiawan, Iyan; Iskandar, Iskandar; Umamah, Nur; Luviantika, Irsa (UNIB Press, 2024)
According to the Ministry of Education and Culture, financial literacy education is very necessary to educate people to be aware and understand how to manage finances wisely. Financial literacy education must be given to children, especially elementary school-age children as early as possible. Introducing financial literacy to children can be done by introducing children to the values ​​of money and the culture of saving. Initial observation results show that most students use all their pocket money for consumption. This is what underlies the importance of strengthening financial literacy for children, especially at the elementary school level. PkM activities are carried out by focusing on introducing financial concepts through introducing nominal money and saving activities by making piggy banks. The training method was carried out in two sessions, namely session 1 with face-to-face presentation of the material by the resource person and session 2 training in making educational media to improve. The activity results showed an increase in students' understanding of financial concepts with active participation and high enthusiasm for using money wisely, as well as fostering a sense of the importance of saving for the future.